Pelatihan Aplikasi Kas Masuk dan Kas Keluar pada Yayasan Alam Tunas Mulia Bantargebang Bekasi - Mardi Yudhi Putra; Nadya Safitri; Ari Nurul Alfian; Ahmad Safei; Rayhan Wahyudin Ratu Lolly (Jurnal Nusantara Mengabdi, 2022)
Purpose: 1) Being able to understand the introduction of website-based applications. 2) Able to use school cash in and cash out applications 3) Able to manage website-based cash report administration. Method: The preparation stage is the identification of partner problems, the implementation stage is the delivery of training materials and discussions. The evaluation stage is to provide training feedback. Results: The activity was attended by 5 participants with the results of feedback related to responses to training materials at a score of 5 (Very Good) 100%. Conclusions: 1) Being able to recognize web-based cash applications as a whole gave a positive response, namely at a score of 5 (very good) 100%. 2) Being able to use cash applications as a whole gives a positive response, namely at a value of 4 (good) 20% and a value of 5 (very good) 80%. 3) Able to manage reports of cash inflows and cash outflows as a whole gave a positive response with a value of 4 (good) 40% and a value of 5 (very good) 60%..